2012
DOI: 10.1108/13639511211215423
|View full text |Cite
|
Sign up to set email alerts
|

Police accreditation and clearance rates

Abstract: Purpose-To examine whether accredited police agencies display higher clearance rates than their non-accredited counterparts. Design/methodology/approach-The study group consists of all municipal police departments operating continuously in the State of Florida from 1997 through 2006. Independent variables capture organizational characteristics for nearly 260 agencies to determine whether becoming accredited improves clearance rates. Findings-Random-effects tobit analysis suggests that accreditation status does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…So if committing crime is not all that hard to do, it might logically follow that one should find it is pretty easy to get away with most criminal activity. This idea is confirmed by research demonstrating that clearance rates for a wide variety of crimes—even really serious ones like armed robbery and homicide—are far from 100 percent (Doerner and Doerner, 2012; Roberts, 2014). Even for crimes like driving while intoxicated—an offense that carries extremely stiff penalties all around the country (Yao, Johnson, and Beck, 2014)—research has indicated that the odds of getting caught can be upwards of 1 in 200 (Beitel, Sharp, and Glauz, 2000).…”
mentioning
confidence: 86%
“…So if committing crime is not all that hard to do, it might logically follow that one should find it is pretty easy to get away with most criminal activity. This idea is confirmed by research demonstrating that clearance rates for a wide variety of crimes—even really serious ones like armed robbery and homicide—are far from 100 percent (Doerner and Doerner, 2012; Roberts, 2014). Even for crimes like driving while intoxicated—an offense that carries extremely stiff penalties all around the country (Yao, Johnson, and Beck, 2014)—research has indicated that the odds of getting caught can be upwards of 1 in 200 (Beitel, Sharp, and Glauz, 2000).…”
mentioning
confidence: 86%
“…In these statistics, homicides are coded as a by-product of another felony – for example, a homicide committed in the course of a robbery is coded as a ‘robbery gone wrong’ rather than a homicide (Finch, 2001). Much of the homicide clearance literature to date relies on data from the United States (Alderden and Lavery, 2007; Davis et al, 2014; Doerner and Doerner, 2012; Jarvis and Regoeczi, 2009; Keel et al, 2009; Litwin and Xu, 2007; Quinet and Nunn, 2014; Regoeczi et al, 2008; Riedel and Boulahanis, 2007; Roberts, 2007; Roberts and Lyons, 2009, 2011; Schroeder and White, 2009; Taylor et al, 2009). So far, it has not been possible to compare homicide clearance rates between European countries, owing to differences in definitions, data sources and criminal justice procedures.…”
Section: Homicide Clearancementioning
confidence: 99%
“…As Cullen (2016) highlights in his broader discussion of the relationship between resource allocations and crime, there is much we do not know. Traditional research on resource allocation and crime has primarily concerned case-level management (i.e., specialized units and deployment of officers), organizational factors (agency size and centralization or decentralization), and contextual or environmental factors (Doerner & Doerner, 2012). Yet, there is also evidence that legal changes and political decisions can affect police outcomes (White, 2003), in addition to standard case and organizational explanations.…”
Section: Introductionmentioning
confidence: 99%